DC-side Harmonic Analysis of SPWM-mode Traction Inverter - GAO Daoxing (机车电传动)
Based on energy conservation principle, DC input harmonics current of the SPWM-mode traction inverter was deducedwith AC-side instantaneous power calculation, and harmonics frequency spectrum of DC-side current was revealed. Then, harmonics ofrailway supply line current and support capacitor current was conducted. A simulation using Matlab/Simulink for an inverter supplied by aDC voltage system was performed, which verified the theoretical analysis in this paper.